A comparative study of the role of selected interior design elements in managing distractions within in-between spaces of UP Diliman - Ortacio, Laarni A.; Florendo, Raquel B. (Quezon City College of Home Economics, University of the Philippines Diliman, 2018)
This study determined the role of selected interior design elements such as furniture type and arrangement, space size and allocation, acoustics, lighting, and heat, ventilation and air condition (HVAC) in managing distractions within two selected in-between spaces in UP Diliman, namely the first floor of Institute of Math and the Skywalk of college of Mass Communication. The participants included thirty (30) survey respondents and ten (10) key informants to the interview. A comparative case study type of research was used eight mixed-method approach. The study used the following instrumentation: for Phase I, an ocular survey, for Phase II, Interior Space Analysis, for Phase III, Survey Questionnaire and for Phase IV, a Semi-Structed Interview. Purposive sampling was used in selecting two in-between spaces and the participants for the interviews. After which, a convenience sampling, and snowball sampling were used to further validate the data. Based on the data gathered, common characteristics of furniture type were free standing and its arrangements were flexible to the type of activity of the students. Students were provided with one type of space for their academic tasks which was commonly illuminated with one type of lighting fixture. This was re-enforced by natural daylight. More often than not, the temperature was observed to be comfortable. With this kind of setup, the students used the space for collaborative type of work. On the contrary, the selected in-between spaces greatly differed in terms of acoustics. However, noise coming from conversations of other users was identified as the most prevailing distraction among them. Typically, the students were not able to alter the conditions of their environment whenever they encounter noise. However, the other interior design elements' role were dependent on the locale of the areas studied.
submitted June 2018
Thesis (B.S. Interior Design)--University of the Philippines Diliman
Keywords: Interior architecture -- Philippines -- Quezon City; University of the Philippines Diliman -- Buildings